Utility of thallium and geochemical analysis of Mariana arc sediments from ODP Hole 129-801A and 129-801B - Julie Prytulak; Sune G Nielsen; Terry Plank; M Barker; T Elliott (PANGAEA, 2016)
We provide the first exploration of thallium (Tl) abundances and stable isotope compositions as potential tracers during arc lava genesis. We present a case study of lavas from the Central Island Province (CIP) of the Mariana arc, supplemented by representative sedimentary and altered oceanic crust (AOC) inputs from ODP Leg 129 Hole 801 outboard of the Mariana trench. Given the large Tl concentration contrast between the mantle and subduction inputs coupled with previously published distinctive Tl isotope signatures of sediment and AOC, the Tl isotope system has great potential to distinguish different inputs to arc lavas. Furthermore, CIP lavas have well-established inter island variability, providing excellent context for the examination of Tl as a new stable isotope tracer. In contrast to previous work (Nielsen et al., 2006b), we do not observe Tl enrichment or light epsilon 205Tl (where epsilon 205Tl is the deviation in parts per 10,000 of a sample 205Tl/203Tl ratio compared to NIST SRM 997 Tl standard) in the Jurassic-aged altered mafic ocean crust subducting outboard of the Marianas (epsilon 205Tl = - 4.4 to 0). The lack of a distinctive epsilon 205Tl signature may be related to secular changes in ocean chemistry. Sediments representative of the major lithologies from ODP Hole Leg 129 801 have 1-2 orders of magnitude of Tl enrichment compared to the CIP lavas, but do not record heavy signatures (epsilon 205Tl = - 3.0 to + 0.4), as previously found in similar sediment types (epsilon 205Tl > + 2.5; Rehkämper et al., 2004). We find a restricted range of epsilon 205Tl = - 1.8 to - 0.4 in CIP lavas, which overlaps with MORB. One lava from Guguan falls outside this range with epsilon 205Tl = + 1.2. Coupled Cs, Tl and Pb systematics of Guguan lavas suggests that this heavy Tl isotope composition may be due to preferential degassing of isotopically light Tl. In general, the low Tl concentrations and limited isotopic range in the CIP lavas is likely due to the unexpectedly narrow range of epsilon 205Tl found in Mariana subduction inputs, coupled with volcaniclastic, rather than pelagic sediment as the dominant source of Tl. Much work remains to better understand the controls on Tl processing through a subduction zone. For example, Tl could be retained in residual phengite, offering the potential exploration of Cs/Tl ratios as a slab thermometer. However, data for Tl partitioning in phengite (and other micas) is required before developing this application further. Establishing a database of Tl concentrations and stable isotopes in subduction zone lavas with different thermal parameters and sedimentary inputs is required for the future use of Tl as a subduction zone tracer.
Supplement to: Prytulak, J et al. (2013): Assessing the utility of thallium and thallium isotopes for tracing subduction zone inputs to the Mariana arc. Chemical Geology, 345, 139-149, https://doi.org/10.1016/j.chemgeo.2013.03.003